Can a Checklist Facilitate Recognition of a Transfusion-Associated Adverse Event by Prelicensure Nurses? - Scott, Sue S; Scanlon, Marcia; McKelvey, Michele; Nathanson, Brian H; Andrzejewski, Jr, Chester (Nurse educator, 2024)
Early identification of a transfusion-associated adverse event (TAAE) is key to patient safety. Research has indicated that use of a TAAE checklist resulted in greater frequency of TAAE recognition behaviors. To explore whether use of a TAAE checklist resulted in greater frequency of TAAE recognition behaviors among nursing students. A prospective, randomized controlled study was conducted with 62 nursing students playing the role of a registered nurse in a simulation of a patient exhibiting clinical indicators of a TAAE. Subjects were randomly assigned to have or not have a TAAE checklist. Time to recognition of the TAAE was measured. The checklist group (CG) identified TAAEs on average 4 minutes sooner than the non-CG ( P < .001). CG subjects were also significantly less likely to miss TAAEs completely. A checklist may improve the safety of transfusions by promoting earlier recognition and treatment of TAAEs.